Pengaruh Penggunaan Gadget Terhadap Hasil Belajar Siswa Kelas VI SD Negeri 11 Parepare - Syamsuddin, jusmiyati87; Nurul Ilmi; Amirah Nurul Inayah; Syamsul Bahar (Journal of Media and Communication Studies, 2024)
Gadget is a technological tool that is made to have good functions, is practical and can facilitate human activities. Where users of this gadget are not only adults, but also many elementary school age (SD) or teenagers who already use gadgets for their various needs. Nowadays, children's social life is more easily affected by gadgets, especially their learning outcomes. The use of gadgets can help children's creativity if their use is balanced with the positive features of these gadgets. But it can also have a negative impact if there is no parental supervision when children use their gadgets. In this study, we will discuss the effect of using gadgets on the learning outcomes of class VI students at SD Negri 11 parepare. This study uses a quantitative research method with expo facto research design or looking for the influence between 2 variables. The results showed that there was no influence between the use of gadgets on the learning outcomes of class VI students at SD Negri 11 Parepare (788 > 0.05)Keywords: